Reconceptualizing Language Acquisition through Embodiment and Materiality - Eka Marcella; Tasya Amin Zakiyah (Pemuda Peduli Publikasi Insan Ilmiah, 2024)
Purpose: This study aims to reconceptualize language acquisition by exploring how embodiment and materiality influence the processes of learning and meaning-making. It challenges traditional cognitive perspectives that separate mind and body by examining how gestures, sensory experience, spatial arrangements, and material objects actively shape linguistic understanding. Subjects and Methods: The study employed a qualitative interpretive design grounded in phenomenology and post humanist theory. Data were collected through participant observation, semi-structured interviews, and artifact analysis in two multilingual classrooms involving twenty-four learners aged ten to fourteen and four language teachers. Thematic and multimodal analyses were conducted to identify patterns of bodily engagement, material mediation, and sensory interaction in language learning. Results: Findings reveal that language acquisition unfolds as an embodied and materially mediated process. Gestures extend linguistic thought, materials such as objects and digital tools act as cognitive mediators, and spatial as well as sensory environments shape learners’ affective and cognitive engagement. The body functions as a site of memory and meaning, where linguistic recall and comprehension are enacted through movement, rhythm, and emotion. Conclusions: Language learning is a multisensory, relational, and embodied experience that integrates cognition, emotion, and material interaction. Pedagogical practices should therefore promote movement, touch, and sensory engagement to enhance comprehension and retention. The study contributes to theoretical and practical understandings of language as a distributed phenomenon emerging through the interplay of human and material agency.